1983
DOI: 10.2170/jjphysiol.33.635
|View full text |Cite
|
Sign up to set email alerts
|

Rate of CO2 diffusion in the human red blood cell measured with pH-sensitive fluorescence.

Abstract: The diffusion rate of C02, into and out of the red cell, was measured by using a stopped flow method with pH-sensitive fluorescence of 4-methylumbelliferone. A red cell suspension of 15 % hematocrit with the Pco2 of 8 Torr (or 65 Torr) was mixed with the same amount of saline solution having 65 Torr (or 8 Torr). Carbonic anhydrase was added to the external solution at a concentration of 20 mg/100 ml in order to accelerate the hydration and dehydration reactions, so that the Pcoz change in the fluid could be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The transfer coefficient of C02 (,(C02)) was also estimated from the numerical solution of the diffusion equation accompanying the HC03 -shift , and from the experimental data on the C02 diffusion and HC03 -shift (NIIZEKI et al, 1983. It was determined to be 2.5 x 10-6 cm • s-1 • Torr-1 similar to the ?J(02).…”
Section: Computation Of (A-v)co2 and (V-a)ccozmentioning
confidence: 99%
“…The transfer coefficient of C02 (,(C02)) was also estimated from the numerical solution of the diffusion equation accompanying the HC03 -shift , and from the experimental data on the C02 diffusion and HC03 -shift (NIIZEKI et al, 1983. It was determined to be 2.5 x 10-6 cm • s-1 • Torr-1 similar to the ?J(02).…”
Section: Computation Of (A-v)co2 and (V-a)ccozmentioning
confidence: 99%
“…His value is apparently short, compared with the value measured by NIIZEKI et al (1983) at the hematocrit of 0.075. This difference may be ascribed to the difference in hematocrit, referring to the computed data of Fig.…”
Section: Discussionmentioning
confidence: 61%
“…(11) (12) 7) Computation of the final extracellular Pco2 and HC03-. The extracellular fluid in the RBC suspension used by NIIzEKI et al (1983) contained carbonic anhydrase of 20 mg/ dl, and therefore, the hydration and dehydration reactions proceeded fairly fast in the fluid, with the equilibrium being established in a short time. Thus, extracellular Pco 2 and HC03-were corrected at each end of the increment time by using the following equation derived from two Henderson-Hasselbalch equations before and after both the C02 diffusion and HC03-shift:…”
Section: Derivation Of Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCHIDA et al [31] measured the C02 diffusion rate in a thin layer of hemoglobin solution, and found that the inward and outward diffusions were equally retarded at the gas-liquid interface. NIIZEKI et al [23,24] measured the C02 diffusion rate in the RBC under lowered convective conditions and found that the value of tj for C02, being 2.5 x 10-6 cm • s-1 • Torr-1, was identical to that for 02 [9,10,16].Oxygenation and deoxygenation reactions of hemoglobin are very fast [20] and hydration and dehydration reactions of C02 are also highly accelerated by carbonic anhydrase in RBC [23]. Thus, the rates of 02 and C02 reactions with RBC are limited by the transfer rates of these gases and HC03 -ion across the RBC interface as well as by the intracellular diffusion rate.…”
mentioning
confidence: 99%